LAMBDA: UNA APLICACIÓN INFORMÁTICA PARA EL ESTUDIO LINGÜÍSTICO - Provencio Garrigós, Herminia; Carrión Plaza, José Carlos (Revista de Investigación Lingüística, 1999)
In this paper, the first version of a software program aimed at the development of linguistic analysis of texts is described. With this version, we have achieved a flexible tool that allows us to obtain information about the structure of the text and the configuration of its lexicon. The text that is used for the demostration of the program is the Spanish Constitution, which permits a perfect visualization of the program capabilities due to its special characteristic as a juridical text.